Physiology of Prenatal Exercise and Fetal Development - May, Linda E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Exercise during pregnancy maintains, and in some cases improves, maternal fitness and physical capacity, significantly decreases risk of developing preeclampsia, hypertension, gestational diabetes mellitus, decreases weight gain, and improves attitude and mental state.  Placental adaptations have been discovered recently that indicate an increase in blood flow and nourishment to the fetus.  This new SpringerBrief in Physiology explores the newest research findings on how exercise influences the fetus in utero and beyond.  Physiology of Prenatal Exercise and Fetal Development reviews the current findings of how maternal exercise throughout gestation influences fetal development of key organ systems, and will also encompass the relationship between maternal activity level and fetal, birth, and neonatal effects.  This information will help researchers and scientists better understand the physiological effects of exercise during pregnancy on offspring development.
Maternal Exercise Throughout Gestation and Fetal Development -- Effects of Maternal Exercise on Labor and Delivery -- Fetal and Postnatal Growth and Development -- Effect on Postnatal Health and Beyond -- What are the barriers and what is OK for an exercise study -- Conclusions.
Keywords: Human physiology; Maternal and child health services; Developmental biology; Obstetrics; Medicine; Human Physiology; Maternal and Child Health; Developmental Biology; Obstetrics/Perinatology/Midwifery.; Biomedicine, general